2005
DOI: 10.1093/brain/awh500
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory activations during the observation of touch and a case of vision–touch synaesthesia

Abstract: In this study, we describe a new form of synaesthesia in which visual perception of touch elicits conscious tactile experiences in the perceiver. We describe a female subject (C) for whom the observation of another person being touched is experienced as tactile stimulation on the equivalent part of C's own body. Apart from this clearly abnormal synesthetic experience, C is healthy and normal in every other way. In this study, we investigate whether C's 'mirrored touch' synesthetic experience is caused by overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
461
5
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(509 citation statements)
references
References 40 publications
34
461
5
9
Order By: Relevance
“…Our findings also provide further support for the existence of a mirror neuron system for touch (Blakemore et al, 2005). When we directly face an individual, as participants did in the present experiment, we often mirror that individual's movements and sensations in a body part (e.g., the left hand) that mirrors the body part that is being manipulated by the observed individual (e.g., the right hand) (Pelphrey et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings also provide further support for the existence of a mirror neuron system for touch (Blakemore et al, 2005). When we directly face an individual, as participants did in the present experiment, we often mirror that individual's movements and sensations in a body part (e.g., the left hand) that mirrors the body part that is being manipulated by the observed individual (e.g., the right hand) (Pelphrey et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…Recent findings indicate that watching a person being touched on a particular part of the body results in the activation of corresponding regions within the perceiver's somatosensory cortex (Blakemore, Bristow, Bird, Frith, & Ward, 2005). Moreover, when we directly face a person, as our study participants directly faced the child, we appear to simulate their experiences in body parts that mirror those of the individual (Pelphrey et al, 2004).…”
Section: A Mirror Neuron System For Touch In the Human Somatosensory mentioning
confidence: 85%
“…Additionally, viewing another person's hand may cause social effects that seeing a rubber hand would not. Recent studies, for example, have found that seeing someone else being touched activates primary and secondary somatosensory cortex in a manner comparable to actual tactile perception (Blakemore et al, 2005;Bufalari et al, 2007;Keysers et al, 2004), suggesting a tactile homologue of the human mirror system (cf. Rizzolatti & Craighero, 2004).…”
Section: Subjective Reports Of Rubber Hand Illusionmentioning
confidence: 99%
“…For example, I can experience touch of an object on my own body, but I cannot have a direct experience of touch on someone else's body. My brain may simulate the experience of touch (Keysers et al, 2004;Thomas, Press, Haggard, 2006), and, in the case of some individuals, the brain appears to actually produce a tactile experience when watching another person being touched (e.g., Blakemore et al, 2005).…”
mentioning
confidence: 99%
“…Such automated, vicarious activations contribute to our understanding of the mental and bodily states of other people and facilitate social interaction [for reviews, see, e.g., Frith and Frith, 2007; Hari and Kujala, 2009]. Although the most prominent vicarious activations have been demonstrated in pre‐motor cortical areas [for a review, see, e.g., Rizzolatti and Craighero, 2004], also somatosensory cortices are engaged during observation of actions [e.g., Avikainen et al, 2002; Möttönen et al, 2005; Oouchida et al, 2004; Rossi et al, 2002] or while seeing other people being touched [e.g., Blakemore et al, 2005; Ebisch et al, 2008; Keysers et al, 2004; Martínez‐Jauand et al, 2012; Meyer et al, 2011; Pihko et al, 2010; Schaefer et al, 2009]. …”
Section: Introductionmentioning
confidence: 99%